Potential hepatoprotective effects of Cistanche deserticola Y.C. Ma: Integrated phytochemical analysis using UPLC-Q-TOF-MS/MS, target network analysis, and experimental assessment - Wang, Haichao; Li, Yaying; Bian, Yifei; Li, Xue; Wang, Yubei; Wu, Ke; Liu, Chuanguo; Liu, Yuhong; Wang, Xiaoming (Frontiers in Pharmacology, 2022)
Background: Cistanche deserticola Ma (CD) has hepatic-protection activity, but the active ingredients and involved mechanism have not been fully explored. Purpose: To explore the components of CD and the hepatic-protection mechanism. Methods: The potential active constituents of phenylethanoid glycosides (PhGs) of CD were studied using ultra-performance liquid chromatography with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS) combined with network pharmacology. A model of L02 cell inflammation induced by lipopolysaccharide (LPS) was confirmed in vitro. Then molecular docking and toll-like receptor 4 (TLR4) target competition experiments were applied to validate the reliability of the core targets. Finally, its hepatoprotective effect was further verified in vivo. Results: Based on UPLC-Q-TOF-MS/MS method, a total of 34 PhGs were identified. Echinacoside (ECH) was identified as the key ingredient, TLR4 and nuclear factor-kappa B (NF-κB) were speculated as the core targets of the hepatoprotective effect of CD via network pharmacology. The in vitro validation experiments confirmed that PhGs had significant anti-inflammatory activity. In addition, molecular biology methods such as western blot and real time quantitative polymerase chain reaction (RT-qPCR) indicated that ECH notably reduced the levels of interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α), as well as the mRNA expression of TLR4, TNF-α and IL-6, and decreased the high expression of TLR4 protein, which in turn down-regulated the high expression of myeloid differentiation factor 88 (MyD88), p-P65 and TNF-α proteins in the inflammatory model. The molecular docking and in vitro target competition experiments demonstrated that ECH displayed high affinity towards TLR4. The results of in vivo studies showed that ECH significantly ameliorated LPS-induced hepatic inflammatory infiltration and liver tissue damage as well as reduced serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in mice. Moreover, ECH remarkably inhibited the release of inflammatory factors such as TNF-α, IL-6, IL-1β and MCP-1 in the serum of mice. Conclusion: ECH exerts its hepatic protection effect through inhibiting the inflammatory response by TLR4/NF-κB signaling pathway. More importantly, ECH can also be used as a potential inhibitor of TLR4. Our results could provide a basis for exploring the hepatoprotection of CD in the future.